تأثير منهج بالألعاب المائية في بعض القدرات الحركية وتعلم المهارات الأساسية للسباحة الحرة للطلاب بأعمار 11-12سنة - سعيد, كةذال كاكه حمه; صالح, محمد مصطفى محمد (Sulaimani Journal for Humanities, 2018)
The aim of the research was to: Identify the effect of water games in some motor abilities and learn the basic skills of the tribal and remote tests of free swimming with ages (11-12) years. The researchers hypothesized: There are significant differences between the tribal and remote tests of some motor abilities and learning the basic skills of free swimming with ages (11-12) years. The researcher used the experimental method to suit the nature of the research problem. The research community was deliberately determined by the students of the sixth grade of primary school (Ahmad Hrdi) in the center of Sulaymaniyah governorate for the academic year (2014-2015) of (21) students and randomly excluded (7) (14) students and ages (11-12) years as a sample for research and by percentage (66%)، representing one experimental group The researchers developed experimental design using a single group، which is subject to pre-test and post-test. The researchers prepared a questionnaire that includes a set of motor skills and basic skills for free swimming and presented to a group of specialists to choose the most suitable. The capacity، mobility and basic skills of free swimming were designed and presented to a number of experts And specialists in this area، and after collecting the forms and unloading data excluded the motor variables that obtained a proportion of less than 60%، since the researchers have the right to choose the proportion that he sees appropriate when choosing the indicators. The most important conclusions are that there are significant differences between the tribal and remote tests of some motor abilities and learning the basic skills of free swimming at the age of (11-12) years and in favor of remote tests. The most important recommendations are the adoption of water games because of their positive influence in developing the most important capacities Physical and motor mobility of learners aged 11-12 years .